2022
DOI: 10.3389/fimmu.2022.930488
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analyses identify RIPOR2 as a genomic instability-associated immune prognostic biomarker in cervical cancer

Abstract: Cervical cancer (CC) is a malignancy that tends to have a poor prognosis when detected at an advanced stage; however, there are few studies on the early detection of CC at the genetic level. The tumor microenvironment (TME) and genomic instability (GI) greatly affect the survival of tumor patients via effects on carcinogenesis, tumor growth, and resistance. It is necessary to identify biomarkers simultaneously correlated with components of the TME and with GI, as these could predict the survival of patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…In agreement, a recent study identified a four gene antitumor signature related to the tumor microenvironment, which included RIPOR2, CCL22, PAMR1, and FBN1 genes [ 54 ]. Authors found that tumors with high expression of RIPOR2, had a lower mutation burden, and higher levels of CD8 + T cells.…”
Section: Discussionsupporting
confidence: 56%
“…In agreement, a recent study identified a four gene antitumor signature related to the tumor microenvironment, which included RIPOR2, CCL22, PAMR1, and FBN1 genes [ 54 ]. Authors found that tumors with high expression of RIPOR2, had a lower mutation burden, and higher levels of CD8 + T cells.…”
Section: Discussionsupporting
confidence: 56%
“…It was shown that RIPOR2 (Rho family-interacting cell polarization regulator 2) exerts inhibitory effects on RHO activity and cellular functions affected by RHO, mainly related to RHO signaling and skeletal muscle cell migration, associated with growth and differentiation [28]. Another impressive finding [29] was the intrinsic relationship between RIPOR2 and T cells, with significantly higher levels of CD 8+ T cells with high RIPOR2 expression. Meanwhile, RIPOR2 has RHOA-dependent effects on various T cell activities, including T cell polarization, adhesion, and migration.…”
Section: Discussionmentioning
confidence: 99%
“…As for TME and genomic instability can greatly affect patients’ prognosis by causing cancer, promoting tumor growth and increasing drug resistance, some hold the view that it is necessary to identify biomarkers which correlate with both TME and genomic instability to predict and evaluate patients’ survival and response to immunotherapy. Combined with comprehensive bioinformatics analysis, RIPOR2 was found to be closely related to tumor mutation burden (TMB), gene expression associated with DNA damage response (such as PARP1), TME-related scores, immune checkpoint activation, and immunotherapy efficacy ( Xu F. et al, 2022 ). Lymph node metastasis of cervical cancer has always been a major obstacle in treatment.…”
Section: Introductionmentioning
confidence: 99%